PDGFRB mutation and tyrosine kinase inhibitor resistance in Ph-like acute lymphoblastic leukemia - Zhang, Yingchi (Blood, 2018)
Philadelphia chromosome (Ph)-like acute lymphoblastic leukemia (ALL) comprises ∼10% to 15% of childhood ALL cases, many of which respond exquisitely to tyrosine kinase inhibitors (TKIs), for example, imatinib in PDGFRB-rearranged ALL. However, some cases developed drug resistance to TKIs and the mechanisms are poorly understood. In this study, we identified a novel PDGFRB fusion gene, namely AGGF1-PDGFRB, and functionally characterized its oncogenic potential in vitro. Further genomic profiling of longitudinally collected samples during treatment revealed the emergence of a mutation, PDGFRB(C843G), which directly conferred resistance to all generations of ABL TKIs, including imatinib, dasatinib, nilotinib, and ponatinib. PDGFRB-mutant leukemia cells are highly sensitive to multitarget kinase inhibitor CHZ868, suggesting potential therapeutic options for some patients resistant to ABL TKIs. In summary, we describe a complex clonal evolution pattern in Ph-like ALL and identified a novel PDGFRB point mutation that drives leukemia relapse after ABL TKI treatment.